UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI DI SMP NEGERI 1 KUBU KABUPATEN ROKAN HILIR - Karsono, - (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Abstract: Based on observations while at SMPN 1 Kubu Rokan Hilir, discovered the phenomenonamong others; The presence of some of the teachers who often come not in time do not even come for no apparent reason, the existence of some teachers who often leave the office during working hours, tasks and activities provided by the school principal told the teacher is not running, as expected, especially when the task the school office after hours. Many of the teachers were not prepared for the learning tools they should have. Remedial and enrichment programs not running as it should, so that learning becomes less than the maximum. This type of research is Action Research School located at SMPN 1 Kubu Rokan Hilir, aimed at teachers. The main reason is of the observations and information from the teacher, that teacher performance is still relatively lacking. Place of research is in SMPN 1 Kubu Rokan Hilir. When the study was conducted in February 2015. The number of samples set out in this study were 20 teachers. From the description of data processing and discussion it was concluded that teacher performance is obtained in the first cycle of 57% with a good category and the second cycleincreased to 80% in both categories. This means that the activity can Improve Teacher Performance Supervision at SMPN 1 Kubu Rokan Hilir is successful.Keywords: Supervision, remedial and enrichment